2022
DOI: 10.1057/s41287-022-00510-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Exposure of Households to Food Insecurity in Uganda: Insights from a National High Frequency Phone Survey

Abstract: We estimate the impact of COVID-19 lockdown induced income shocks on household food insecurity outcomes in Uganda using five rounds of a nationally representative High Frequency Phone Survey. Relative to the baseline survey conducted just before the pandemic, there was a significant decrease in households' participation in wage work, agricultural production, and non-farm business which in turn increased their income losses. Consequently, we find that lockdown induced income losses significantly increased incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Likewise, it was found that FI was positively associated with the number of individuals aged from 5 to 18 years, the illness, accident, or death of an income-earning household member, and health expenditure due to COVID-19 or another illness, as well as the increase in the prices of food consumed, reduced family income, and job loss by any member of the household. These factors that were associated with a higher prevalence of FI have been observed in studies conducted in other geographical contexts, such as Ethiopia [ 27 ], Uganda [ 25 , 46 ], Kenya [ 46 ], Bangladesh [ 35 ], Australia [ 12 ], and other countries belonging to the sub-Saharan African region [ 26 ]. These findings can be attributed to the main effects of the COVID-19 pandemic on various socioeconomic aspects of the populations of low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Likewise, it was found that FI was positively associated with the number of individuals aged from 5 to 18 years, the illness, accident, or death of an income-earning household member, and health expenditure due to COVID-19 or another illness, as well as the increase in the prices of food consumed, reduced family income, and job loss by any member of the household. These factors that were associated with a higher prevalence of FI have been observed in studies conducted in other geographical contexts, such as Ethiopia [ 27 ], Uganda [ 25 , 46 ], Kenya [ 46 ], Bangladesh [ 35 ], Australia [ 12 ], and other countries belonging to the sub-Saharan African region [ 26 ]. These findings can be attributed to the main effects of the COVID-19 pandemic on various socioeconomic aspects of the populations of low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 64%
“…Based on previous studies using the HFPS [ 25 , 26 , 27 ], we included the following predictors: the location of the household (non-capital/capital), number of bedrooms, number of individuals aged between 5 and 18 years, number of male individuals in the household, the illness, accident, or death of an income-earning household member (yes/no), health expenditure associated with COVID-19 or another illness (yes/no), rising prices of food consumed in the household (yes/no), family income during the pandemic (increased/remained equal/decreased), and whether a household member received cash, a check, or transfer from a government institution, non-government institutions, companies, or religious institutions (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…The impacts of the loss of income from employment and income-generating activities on diets can be through loss of purchasing power (30). The effects of COVID-19 related income shocks on food security and diets have been reported in Uganda and Kenya, with poor households most affected (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In general, ICTs can enable faster access to updated data from farming households, thus enabling appropriate interventions tailored to a food system's current needs. For instance, Agamile (2022) and Tortorella et al (2022) used a High-Frequency Phone Surveys (HFPS) ICT strategy to collect household consumption data at monthly intervals during the COVID-19 lockdown, because face-to-face interviews could not be used. Agamile (2022), indicated that indeed the lockdown had induced income losses significantly, reduced access to farminputs, and increased incidences of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Agamile (2022) and Tortorella et al (2022) used a High-Frequency Phone Surveys (HFPS) ICT strategy to collect household consumption data at monthly intervals during the COVID-19 lockdown, because face-to-face interviews could not be used. Agamile (2022), indicated that indeed the lockdown had induced income losses significantly, reduced access to farminputs, and increased incidences of food insecurity. These findings fostered government initiatives to support food consumption for the vulnerable communities (especially those in urban slums).…”
Section: Introductionmentioning
confidence: 99%